Pendidikan Seks Bagi Remaja Menurut Abdullah Nasih Ulwan - Saputra, Muhammad Indra (Universitas Islam Negeri Raden Intan Lampung, 2016)
Reproductive health, in this case, is the Sex and the problem is difficult to solve. During this time people view sex as